1989
DOI: 10.1007/bf02554499
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from ischemic colitis

Abstract: Thirty-nine hospital-based cases of ischemic colitis were reviewed. There were 18 males and 21 females. Average age was 68.7 years (range, 18 to 92 years). Associated diseases among 13 patients younger than 65 included renal failure in seven patients and hematologic, vasculitic, or collagen vascular diseases in four. In 26 patients 65 or older, congestive heart failure was seen in 13, vascular disease in eight, and previous aortic surgery in four. Nineteen patients were treated nonsurgically and 8 died (42 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 7 publications
4
60
1
3
Order By: Relevance
“…Therefore, any portion of the bowel may be affected, but the sites most often affected are the sigmoid colon, ascending colon and splenic flexure. In systemic low-flow states, the right colon is most often involved, while localized nonocclusive ischemia affects watershed areas, such as the splenic flexure and the sigmoido-rectal junction (Guttormson and Bubrick 1989). Ligation or occlusion of the inferior mesenteric artery produces changes of the sigmoid colon, although changes may be more extensive, if other vessels have been previously occluded.…”
Section: Pathogenesismentioning
confidence: 99%
“…Therefore, any portion of the bowel may be affected, but the sites most often affected are the sigmoid colon, ascending colon and splenic flexure. In systemic low-flow states, the right colon is most often involved, while localized nonocclusive ischemia affects watershed areas, such as the splenic flexure and the sigmoido-rectal junction (Guttormson and Bubrick 1989). Ligation or occlusion of the inferior mesenteric artery produces changes of the sigmoid colon, although changes may be more extensive, if other vessels have been previously occluded.…”
Section: Pathogenesismentioning
confidence: 99%
“…In another retrospective study Guttormson and Bubrick (1989) found the sigmoid colon to be involved in 25.6% of colonic ischemia. Again the diagnosis was made during surgery, by means of endoscopy or a barium enema.…”
Section: Resultsmentioning
confidence: 93%
“…The clinical course of the ischemic colitis is divided in two major groups of patients with gangrene form (15-20%) and patients with non-gangrene form (80-85%). In the nongangrene form the lesions can be transient and reversible, and can progress to chronic and non-reversible stenosis (10-15%) or chronic segmented colitis (20-25%) (Gandhi et al, 1996;Guttormson and Bubrick, 1989). In the beginning, the clinical manifestations in most of patients are non-specific and start with moderate abdominal pain from the engaged by ischemia part of intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Several major studies, related to the disease, found the frequency -5-10/100 000. It is found most frequently in women and in patients above the age of 65 years (Guttormson and Bubrick, 1989;Klempnauer et al 1997;Longo et al, 1997). Although the modern diagnostic options allow the disease diagnosis in the early phases of its development, it, even though rarely, manifests with some of the occurred complications (hemorrhage or stenosis), which require emergency surgical intervention.…”
Section: Introductionmentioning
confidence: 99%